Transcriptome and metabolome analysis of senescent rice (Oryza sativa L.) seeds: insights into the mechanism of germination vigor and seedling morphogenesis - Jingxin Huo; Dianfeng Zheng; Naijie Feng; Rui Zhang; Yingbin Xue; Aaqil Khan; Hang Zhou; Xuefeng Shen; Liming Zhao; Yifei Li; Xiaojun Liu; Junjie Liu; et al. (BMC Plant Biology)
Abstract Seeds germination and seedlings growth are crucial factors in ensuring effective rice grain productivity. However, the mechanisms for maintaining seed vigor remains largely unknown. The seed aging phenomenon that occurs during storage poses a significant challenge to crop production, as it can lead to reduced germination rates and impaired seed vitality. The current study explored the underlying mechanisms that enable rice seeds to maintain high germination rates and seedling vigor after long - term storage. We employed transcriptomic and metabolomic techniques to identify metabolic changes and key genes associated with the aging of rice seeds during long - term storage. We utilized indicators such as imbibition rate (IR), germination rate (GR), mean germination time (MGT), germination coefficient (GC), germination index (GI), and germination potential (GP) to comprehensively assess germination activity. Traits including seedling emergence rate, seedling strength index, photosynthetic parameters, carbohydrate accumulation, and enzyme activity related to carbon metabolism were used to determine the impact of seed storage duration on seedling growth. Our research findings revealed significant differences in gene expression patterns and metabolic characteristics among seeds stored for different duration. Notably, IAA levels, the IAA/ABA ratio, and linoleic acid metabolism were identified as key factors affecting germination and seedling development. Results indicated that with the extension of storage duration, the germination potential and seedling development significantly declined. Current study provided a comprehensive understanding of the physiological and molecular mechanisms behind the germination and morphogenesis of rice seeds under different storage years. The insights gained from this study could be utilized to improve the storage and quality control of rice seeds, thereby ultimately enhancing agricultural productivity.